2022
DOI: 10.1021/acs.nanolett.1c03671
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Lead Halide Perovskite Nanocrystals as a Spin Laser Gain Medium

Abstract: Spin-polarized charge endows conventional lasers with not only new functionalities but also reduced lasing thresholds thanks to the lifting of spin degeneracy. II−VI and III−V semiconductors have been extensively investigated as spin laser gain mediums; however, the degree of polarization is limited by the light hole and heavy hole degeneracy. Herein, we evaluate the potential of CsPbBr 3 nanocrystalsones that are featured with low band-edge degeneracy and therefore a high degree of polarization as a result o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…In a spintronic device, information is recorded in the spin-polarized state of electrons or holes, and the intrinsic spin-relaxation time (longitudinal spin-flip time, T 1 ) thus plays an important role in determining the device performance. A longer spin-relaxation time is usually an essential prerequisite for practical use in spintronic devices. However, the strong SOC effect in LHPs, on the other side, can also reduce the spin-relaxation time (usually down to a few ps), which in turn limits their spin-related applications.…”
mentioning
confidence: 99%
“…In a spintronic device, information is recorded in the spin-polarized state of electrons or holes, and the intrinsic spin-relaxation time (longitudinal spin-flip time, T 1 ) thus plays an important role in determining the device performance. A longer spin-relaxation time is usually an essential prerequisite for practical use in spintronic devices. However, the strong SOC effect in LHPs, on the other side, can also reduce the spin-relaxation time (usually down to a few ps), which in turn limits their spin-related applications.…”
mentioning
confidence: 99%
“…For the case of CsPbBr 3 NCs, it was found that the optical gain threshold could be depressed by polarizing the charge using circularly polarized photoexcitation. Nevertheless, the spin relaxation time was too short to realize a spin laser ( Tang et al., 2022 ). If the spin relaxation time could be prolonged, the threshold reduction would be more remarkable under quasi-continuous wave photoexcitations.…”
Section: Applicationsmentioning
confidence: 99%
“…All‐inorganic cesium lead halide (CsPbX 3 , X = Cl, Br, I) perovskite materials have recently evoked considerable attention in the fields of solar cells, [ 1 ] laser, [ 2 ] and photodetectors, [ 3 ] owing to their outstanding optoelectronic performance, such as large absorption coefficient, high photoluminescence quantum yield (PLQY), narrow emission band, and tunable bandgap. These superior features make CsPbX 3 perovskites ideal candidates as light‐harvesting and light‐emitting materials for a variety of optoelectronic [ 4 ] and photovoltaic [ 5 ] applications.…”
Section: Introductionmentioning
confidence: 99%